Biocontrol of Phytophthora Blight of Red Pepper Caused by Phytophthora capsici Using Bacillus subtilis AH18 and B. licheniformis K11 Formulations - Lim, J.H., Yeungnam University, Gyeongsan, Republic of Korea; Kim, S.D., Yeungnam University, Gyeongsan, Republic of Korea (Applied biological chemistry, 2010)
Bacillus subtilis AH18 and B. licheniformis K11 are multi-functional plant growth-promoting rhizobacteria (PGPR) that promote growth of red peppers and suppress phytophtora blight caused by Phytophtora capsici. A formulation of the two Bacillus strains was developed by producing heat-shocked endospores that had increased heat resistance. For large-scale cultivation in an 8-L jar fermentor, optimal culture conditions were pH 6.8, fermentation temperature of 30, and agitation speed of 180 rpm, with antifoaming agents added at a ventilation condition of 0.8 vvm. Induction of vegetative growth was achieved using 5.0×10∨-6M dipicolinic acid and 7.0×10-⁴M CaCl₂. The subsequent large-scale cultivation produced viable cell numbers of 10∨9 colony forming units/mL. High and low temperature stability tests of pilot products subjected to extreme storage conditions in accordance with thermal stability test standards revealed that storage for up to three years was possible without adverse effects. The combined use of two Bacillus microbial agents in vivo synergistically suppressed phytophthora blight, even following storage of the bacterial formulation at 54℃ for 6 weeks. In field tests involving a phytophthora blight outbreak in red pepper, 40% of untreated peppers died, whereas 80% of peppers treated with the bacterial formulation survived for 65 days. The results indicate the potential of the B. subtilis AH18 and B. licheniformis K11 co-treatment for organic pepper farming.